Measuring the through-plane and in-plane oxygen apparent diffusion coefficients in the gas diffusion layer - Yao, Keguang; Long, Tiehan; Wang, Yajun; Yuan, Xiao-Zi; Yao, Yao; Wang, Haijiang (Frontiers in Energy Research, 2023)
Accurately predicting oxygen mass transport resistance and current distribution in fuel cells requires significant knowledge of oxygen diffusion coefficients in both in-plane and through-plane directions. However, there are few methods for measuring in-plane oxygen diffusion coefficients, which are important parameters for simulating oxygen flux distribution in gas diffusion layers (GDLs). In this study, we establish measurement methods and calculations for both in-plane and through-plane oxygen diffusion coefficients. Using in-house designed cells, we measure the in-plane and through-plane oxygen apparent diffusion coefficients of a commercial carbon paper (AvCarb EP40) at various torques and gas flow rates. We also simulate oxygen flux distributions in the GDL under each torque and gas flow rate. Our results show that the channel part is the major contributor to total oxygen flux at high torque conditions and that an increase in torque leads to a decrease in the contribution from the land part. Simulation results also suggest that a higher gas flow rate and lower torque contribute to a more uniform distribution of oxygen flux in the GDL.